2002
DOI: 10.1007/s00122-002-0864-x
|View full text |Cite
|
Sign up to set email alerts
|

A reference map of Cucumis melo based on two recombinant inbred line populations

Abstract: A composite genetic melon map was generated based on two recombinant inbred line (RI) populations. By analyzing the segregation of 346 AFLPs, 113 IMAs and phenotypic characters on a RI population of 163 individuals derived from the cross Védrantais x PI 161375, a first map was constructed. About 20% of the molecular markers were skewed, and the residual heterozygosity was estimated at 4.43% which was not significantly different from the theoretical value of 4.2%. The genome distribution of molecular markers am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
130
1
11

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 76 publications
(95 reference statements)
5
130
1
11
Order By: Relevance
“…PØrin et al (2002b) reported six FS QTLs in two populations of recombinant inbred lines. Comparing the position of the QTLs reported by those authors with the position presented in the current report and taking into account the co-linearity between both genetic maps (PØrin et al 2002a), it can be deduced that four QTLs have been detected in common: fs1.1, fs.5.1, fs6.1or fs6.2 and fs11.1 may correspond to fs8.1 or fs8.2, fs11.1, fs1.1 and fs12. 1, respectively, in PØrin et al (2002b).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…PØrin et al (2002b) reported six FS QTLs in two populations of recombinant inbred lines. Comparing the position of the QTLs reported by those authors with the position presented in the current report and taking into account the co-linearity between both genetic maps (PØrin et al 2002a), it can be deduced that four QTLs have been detected in common: fs1.1, fs.5.1, fs6.1or fs6.2 and fs11.1 may correspond to fs8.1 or fs8.2, fs11.1, fs1.1 and fs12. 1, respectively, in PØrin et al (2002b).…”
Section: Discussionmentioning
confidence: 89%
“…Altogether, these data confirm that C. melo is one of the most diverse species of the genus Cucumis, although the genetic control of its phenotypic variation is largely unknown. Over 100 genes involved on morphological traits and disease resistance have been reported (Pitrat 1998), and 20 of them have been recently mapped (PØrin et al 2002a). These mapped genes should represent only a very small fraction of the genes underlying the phenotypic variation observed in melon germplasm.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…While Baudarcco-Arnas and Pitrat (1996) produced the first genetic map of melon with 102 RAPD and RFLP markers, this was quickly followed by Wang et al (1997) using 188 predominantly AFLP markers (Table 5.1). Using two RIL populations sharing one common parent, Périn et al (2002a) constructed a high-density composite map using co-migrating AFLP and IMA markers as anchor points. The composite map consists of 668 AFLP, IMA, and phenotypic markers.…”
Section: Molecular Genetic Mapsmentioning
confidence: 99%
“…Since cucurbit breeding places great emphasis on disease resistance, mapping populations used often segregated for more than one disease resistance gene. For example, in melon, MR-1 used by Wang et al (1997) was resistant to fusarium wilt (Fom-1 and Fom-2), downy and powdery mildews; Vedrantais and PI 161375 used by Baudarcco-Arnas and Pitrat (1996) and Périn et al (1998Périn et al ( , 2002a were resistant to fusarium wilt (Fom-1 and Fom-2), and melon necortic spot virus (nsv), and aphid (Vat), respectively; PI 161375 × Pinyonet Piel de Sapo used by Oliver et al (2001) segregated for both nsv and Vat . Populations used by Liou et al (1998), Fukino et al (2002, and Silberstein et al (2003) also segregated for disease resistance in addition to other horticultural traits.…”
Section: Molecular Genetic Mapsmentioning
confidence: 99%